2018
DOI: 10.31983/jkb.v8i2.3738
|View full text |Cite
|
Sign up to set email alerts
|

Terapi Murottal Sebagai Upaya Menurunkan Kecemasan Dan Tekanan Darah Pada Ibu Hamil Dengan Preeklampsia : Literature Review Dilengkapi Studi Kasus

Abstract: The maternal mortality rate (MMR) in Indonesia is far from being the target of sustainable development goal's (SDG's), with one of the dominant causes being hypertension in pregnancy (HDK) such as preeclampsia. Pregnant women with preeclampsia are prone to experience anxiety, which if left untreated will have an effect on the welfare of the mother and baby. Anxiety can also cause blood pressure to raise. One relaxation technique to reduce anxiety and blood pressure is with murottal therapy. The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 1 publication
1
9
0
5
Order By: Relevance
“…Listening Murattal would cause a calm and relaxing effect on a person so that it would also contribute to reducing the blood pressure, anxiety levels and pain intensity. 6 The result showed that Murattal Surah Yusuf Therapy influenced blood pressure causing reduction of blood pressure among pregnant women who had pre-eclampsia. The result showed a significant decrease in blood pressure seen from the difference in average blood pressure before and after the Murattal Surah Yusuf Therapy for 15 minutes, which amounted to 11.104 mmHg at systolic pressure and 7.578 mmHg at diastolic pressure.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Listening Murattal would cause a calm and relaxing effect on a person so that it would also contribute to reducing the blood pressure, anxiety levels and pain intensity. 6 The result showed that Murattal Surah Yusuf Therapy influenced blood pressure causing reduction of blood pressure among pregnant women who had pre-eclampsia. The result showed a significant decrease in blood pressure seen from the difference in average blood pressure before and after the Murattal Surah Yusuf Therapy for 15 minutes, which amounted to 11.104 mmHg at systolic pressure and 7.578 mmHg at diastolic pressure.…”
Section: Discussionmentioning
confidence: 98%
“…Listening to Murattal will have a calming and relaxing effect on a person so that it will also contribute to the reduction in blood pressure. 6 According to Kartini, the Murattal Alqur'an technique is proven to provide a calm and relaxing effect because it provides a positive perception response which can further stimulate the hypothalamus to release endorphins which are hormones that make a person feel happy so that they can reduce the blood pressure. 7 Kartini's research is also supported by the results of research from Diki 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Menghadapi proses persalinan merupakan salah satu faktor yang dapat menimbulkan kecemasan, dimana mengingat proses melahirkan bayi tidak selalu somatic sifatnya akan tetapi bersifat psikosomatic, sebab banyak elemen psikis ikut mempengaruhi kelancaran atau kelambatan proses melahirkan bayi tersebut. Kecemasan akan meningkat pada saat ibu merasakan tanda-tanda kesakitan melahirkan bayinya (Yuliani & Widyawati, 2018).…”
Section: Hasil Dan Pembahasanunclassified
“…Gejala pre eklamsia memiliki tanda-tanda hipertensi diselingi dengan edema dan proteinurine yang muncul ini biasanya terjadi triwulan ketiga atau sebelumnya pada saat kehamilan (kehamilan abnormal) [1]. Gejala Pre eklamsia terjadi kepada ibu hamil, setelah bersalin serta dalam keadaan masa nifas yang terdiri tiga tahapan atau biasa disebut dengan trias yaitu hipertensi, proteinurin dan pembengkakan pada kaki, kadang-kadang disertai kejang-kejang hingga koma, karena tidak menunjukkan adanya kelainan vaskuler atau hiertensi sebelumnya [4].…”
Section: A Pre Eklamsiaunclassified